The Impact of Feed Management Technologies on Mineral Oil Hydrocarbons (MOH) Contamination: A Comparative Farm Level Approach - Mădălina Matei; Silvia Ioana Petrescu; Bianca Maria Mădescu; Dragoș Mihai Lăpușneanu; Daniel Simeanu; Paul Corneliu Boișteanu; Ioan Mircea Pop (Agriculture)
Legislative frameworks about contamination are often limited to foods and underestimate the role of animal nutrition for safe production. This study aims to assess mineral oil hydrocarbon (MOH) contamination in feed and identify the technological factors that are contributing to this issue, particularly focused on mechanised harvesting and processing. Three dairy farms, classified by contamination risk (low, medium, and high), were selected, and fifteen feed samples were analysed using the coupled liquid chromatography–gas chromatography–flame ionisation detection (LC–GC–FID) method, with a microwave-assisted saponification (MAS) step to determine mineral oil saturated (MOSH) and aromatic (MOAH) hydrocarbon levels. Important contamination levels were observed depending on the technological development of each farm. MOSH levels ranged from 11.4 mg/kg to 81.40 mg/kg, while MOAH levels ranged from 0.5 mg/kg to 4.6 mg/kg. MOAH accounted for 4.74% of the total MOH content. The results showed a connection between feed production technologies and MOH contamination levels. Factors such as the mechanisation, the machinery used, and the storage conditions were potentially contributors to contamination, while chemical treatments had no direct impact but some potential risks. The contamination levels varied across farms, indicating certain contamination sources beyond technological factors. Advanced technological measures and proper equipment maintenance are suggested to mitigate MOH contamination risks in feed.